The Importance of Islamic Religious Education in Forming Students Character - Elisa Gustianti; Marsi Dhini Ramadhani; Sri Wahyuni (Cipta Pustaka Nusantara, 2025)
This article presents a presentation about the role of Islamic religious education for the process of forming religious character for students. Islamic religious education is the most important foundation that realizes charachter education.. Education according to these important components is also believed to have an effective role in the formation of student character, especially in realizing the religious character, without ignoring the important things of the contents that associated with Islamic religious education. Where stakeholders in the live of students with religious character models both in the world and in the hereafter. The growth and development of a human identity can begin with the religious soul embedded in the students. This is where the meaning of character education is, therefore the material of Islamic religious education taught in the school environment is one of the supporting values that underlie character education. Through Islamic religious education, students are taught aqidah when they are able to recognize elements. Islamic religious education is education that teaches religious teachings based ob the Qur’an and hadist by using guidelines to protect themself in life. The main objective of Islamic religious education is to shape the personality of students in the context that reflection when behaving and determining thought patterns in life. In addition, the success value of various types of islamic religious education learning in the school environment can be determined by example of appropriate learning methods that are of interest to students.